(untitled) (International Journal of Communication Systems and Network Technologies, 2022)
This research paper outlines the development of a patch antenna using Coplanar Waveguide (CPW) feeding and Defected Ground Structure (DGS) for use in 5G applications operating below 6GHz. The antenna design was simulated using CST numerical analysis software and is intended to operate within a frequency spectrum 3.2GHz - 3.5GHz. Antenna involves a circular patch antenna with ring shaped slot modified with CPW feeding. The antenna is of compact size 45 mm × 45 mm × 0.035 mm and obtains a huge gain which is 6.05dBi and highest directivity of 7.0dB at 3.5GHz frequency. The antenna achieves a radiation efficiency of 88% and a VSWR of less than 2 across the sub 6GHz 5G frequency range. Thus, the intended antenna is a promising for SUB 6GHz 5G applications, offering a broad bandwidth, compact size, and stable radiation characteristics.